2014
DOI: 10.1371/journal.pone.0096609
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of DNA Vaccine Encoding Pseudomonas Exotoxin A and PcrV against Acute Pulmonary P. aeruginosa Infection

Abstract: Infections with Pseudomonas aeruginosa have been a long-standing challenge for clinical therapy because of complex pathogenesis and resistance to antibiotics, thus attaching importance to explore effective vaccines for prevention and treatment. In the present study, we constructed a novel DNA vaccine by inserting mutated gene toxAm encoding Pseudomonas Exotoxin A and gene pcrV encoding tip protein of the type III secretion system into respective sites of a eukaryotic plasmid pIRES, named pIRES-toxAm-pcrV, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Although translocation inhibition of type III secretory toxins by anti‐PcrV antibodies has been suggested to be the main mechanism of the PcrV vaccine, activation of cellular immunity by CpG ODN could be helpful against P. aeruginosa . Previous studies have shown the effectiveness of CpG ODN as an adjuvant in a P. aeruginosa vaccine consisting of O‐polysaccharide from serotype IATS‐1 coupled with Toxin A , and in a DNA vaccine containing genes encoding Exotoxin A and PcrV . Moreover, in a Yersinia pestis vaccine study, a multiple antigen peptide synthesized from LcrV, a V antigen with homology to PcrV, was shown to be highly effective when combined with CpG ODN .…”
Section: Discussionmentioning
confidence: 99%
“…Although translocation inhibition of type III secretory toxins by anti‐PcrV antibodies has been suggested to be the main mechanism of the PcrV vaccine, activation of cellular immunity by CpG ODN could be helpful against P. aeruginosa . Previous studies have shown the effectiveness of CpG ODN as an adjuvant in a P. aeruginosa vaccine consisting of O‐polysaccharide from serotype IATS‐1 coupled with Toxin A , and in a DNA vaccine containing genes encoding Exotoxin A and PcrV . Moreover, in a Yersinia pestis vaccine study, a multiple antigen peptide synthesized from LcrV, a V antigen with homology to PcrV, was shown to be highly effective when combined with CpG ODN .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using adenovirus-based and DNA vaccine strategies incorporating different epitopes against P. aeruginosa have been considered attractive approaches that provide immunogenic and protective responses in animal models [186][187][188][189]. A recent study reported that antipseudmonal vaccines cannot be recommended in cystic fibrosis patients [190]; however, this cannot be generally concluded for other antipseudomonal vaccines in other infections in which further studies are required.…”
Section: Vaccines Immunotherapy and Phage Therapymentioning
confidence: 99%
“…In prophylactic strategies, active immunization against PcrV ensures the survival of challenged mice and decreases lung inflammation and injury [ 89 ]. DNA vaccination with pIRES-toxAm-pcrV has been proposed as a potential immunotherapy [ 90 ]. In passive immunization, the rabbit polyclonal anti-PcrV antibody and murine monoclonal anti-PcrV antibody mAb166 inhibit TTS toxin translocation [ 91 - 95 ].…”
Section: Potential Therapeutic Strategies Against Exou-derived Cytotomentioning
confidence: 99%